AB0064 Spontaneous adipogenesis in bone marrow derived mesenchymal stromal cells after chronic treatment with glucocorticoids. (23rd January 2014) - Tani, C.; Vagnani, S.; Carli, L.; Querci, F.; Baldini, C.; Talarico, R.; Della Rossa, A.; Bombardieri, S.; Mosca, M.
Abstract : Background: Mesenchymal stromal cells (MSCs) are a promising therapeutic tool for many inflammatory autoimmune diseases because of their immunosuppressive potential. MSCs autologous transplantation showed less therapeutic efficacy respect to the allogenic ;a defective MSCs function in patients with autoimmune disease is considered the most important cause. It has been postulated that among many - factors, underlying therapies could interfere with MSCs functions. Objectives: The present study was designed to test the hypothesis that in vivo chronic glucocorticoid treatment (GC) might interfere with MSCs ex vivo proliferation and differentiation capabilities. Methods: Five C57BL6 mice were daily treated with oral 6 metilprednisolone (0.05 mg/Kg body weight) starting from 12 weeks of age. Age-matched C57BL6 untreated mice were used as a control group. Mice were sacrificed at 30 weeks of age, bone marrow was harvested from tibias and femurs from each mouse and mononuclear cells were plated at the density of 300000 cell/cm 2 . Bone-marrow derived mesenchymal stromal cells (bmMSCs) were isolated ad expanded in standard medium for murine MSC culture. Cells were cultured in an incubator at 37°C, 5% humidified CO2 and regularly monitored. Clonogenic potential was evaluated by CFU assay and population doubling (PD) analysis was performed to evaluate the culture growth curve. Cell sorting analysis was performed to evaluate the expression of the following surface marker antigens: Sca-1, CD90.2, CD45, CD106, CD34. Results: The mean CFU frequency 7 and 14 days after seeding resulted 6.25 x10 -7 (±2.3 x10 -7 ) and 14.75x10 -7 (±2.2 x 10 -7 ) respectively in treated mice and 6.4 x10 -7 (±7.4 x10 -7 ) and 11 x 10 -7 (±7.4 x 10 -7 ) in untreated mice; no statistically significant differences were observed at 7 days nor at 14 days (p=0.48 and p=0.25 respectively). As expressed by linear regression analysis, the cumulative PD and the growth curve resulted similar for both treated and untreated mice (y = 0, 0789x-5, 0344 R 2 = 0, 7263 in treated and y=0, 0769x-3, 8475R 2 = 0, 8202 in untreated mice respectively). Under specific differentiation conditioning medium, both groups showed similar qualitative osteogenic and adipogenic potential. However, bmMSCs from treated mice showed spontaneous lipid vesicle accumulation starting from the second culture passage and reaching a wide distribution among cells after six passages while in bmMSC cultures from untreated mice mild spontaneous lipids accumulation was observed after the 14 th passage. Conclusions: It is widely accepted that GC in vitro affect the differentiation of mesenchymal stem cells, through activating or inhibiting the related transcript regulators of osteogenesis and adipogenesis. Our data show that an in vivo treatment with low dose GC for 18 weeks in C57BL6 mice does not alter the frequency and clonogenicity of ex vivo expanded bmMSC nor the proliferation rate. However, the treatment induces early lipid drops accumulation suggesting early spontaneous adipogenesis. If confirmed in future studies, this may constitute an important issue to be considered when evaluating the functional properties of bmMSC from patients with systemic autoimmune diseases under chronic GC treatment. Disclosure of Interest: None Declared